Effectiveness of Printed Modules in the Performance of Grade VI Learners in Science of Baquioen Elementary School - ABARRA, ALEXANDER (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
The primary goal of this action research was to assess the effectiveness of printed modules on the performance of Grade VI pupils in Science during the school year 2021-2022 at Baquioen Elementary School, Sual District, SDO I Pangasinan. Specifically, this study aimed to determine the performance of the Grade VI pupils in science during the pre-test and post-test. It also sought to find answers if there is a significant difference in the performance of the respondents after utilizing printed modules in 8 weeks. This action research project utilized the quasi-experimental method, more especially the single group pre-test and post-test design. An independent variable is changed in a quasi-experiment without participants being randomly assigned to one condition or another. The primary tools used to acquire the required data were the pre-and post-test questionnaires. The researcher developed these questionnaires, and the master teacher in charge of testing then validated them. The school principal gave his approval before things were put into practice. The statistical methods employed to address the specific questions were the main and t-test. Based on the results found there was a significant improvement in the performance of the respondents after they were exposed to printed modules in 8 weeks with a mean difference of 10.48. Therefore, it was proven that there is a significant difference between the scores of pre-test and post-test. Thus, the hypothesis was rejected.